Retroeconomics - Moving from Dying to Brisk Economy - Papava, Vladimer (Journal of Reviews on Global Economics, 2017)
The paper offers a new concept of the technological backwardness in many, mostly in poor countries - the retroeconomics. The goal of the research is to set out the main reasons why in many (and first of all in poor) countries the economies used obsolete technologies. Such countries are getting to into the trap of technological dependency on the economically developed countries. The feasible tools for a technological leap from such dependency are discussed. The main threat of the preservation of the retroeconomy - its zombification is discussed as a main barrier for technological updating of economy, and in general as an obstacle for Schumpeterian creative destruction. Much importance is given to the key principle of bankruptcy procedures against zombified retro-firms. The bankruptcy legislation should ensure the timely liquidation of non-viable firms. A country's legislative framework should strive for the establishment of a sound legal space on the market, when only really viable firms will exist. The role of the government is very important to resolve the problem of the technological backwardness.